Fresco Fragments from Villa Arianna Excavated by Expedition of the State Hermitage: Art as a Mass Archeological Material - Butyagin, Alexander M. (Actual Problems of Theory and History of Art, 2015)
A large number of fragments of frescos from walls and a ceiling of open rooms, was found in Stabiae, which was lost in the eructation of Vesuvius in 79 AD, were discovered during excavations of expedition of the State Hermitage on Ariadna’s villa. The technique of fragments classification depending on the remained image on them was developed for the purpose of their mass studying. It is facilitated by the standard organization of villas’ wall painting compositions. The PANTONE system was used for unification of color definition. Statistical processing of the received results allowed to divide fragments from different rooms moved during destruction of buildings and last excavations. Paintings from the lost parts of walls and the ceiling are taken to a correct restoration also.